Combustible cigarette smoking and alternative tobacco use in a sample of youth transitioning from foster care. (January 2019) - Braciszewski, Jordan M.; Vose-O'Neal, Adam; Gamarel, Kristi E.; Colby, Suzanne M.
Abstract: Among the struggles faced by youth currently in or recently exiting foster care, tobacco use remains a low priority for practitioners and researchers, alike. Indeed, despite the dramatically altered landscape of tobacco products on the market, there have been no studies evaluating the use of alternative tobacco products among this vulnerable population. The current study aimed to determine the prevalence of lifetime and current combustible and non-combustible tobacco use among youth exiting foster care, and report on the prevalence of nicotine dependence, motivation to quit, and preferred methods of tobacco cessation. Youth aged 18–24 ( M = 20.13, SD = 1.16) who were transitioning from foster care ( N = 154) completed a survey of tobacco product use adapted from the Population Assessment of Tobacco and Health Baseline Survey. Most participants (76%) reported lifetime use of combustible cigarettes, while almost half (42%) were current combustible cigarette smokers. Current use of electronic cigarettes was comparable to general population rates. Many participants (76%) reported interest in quitting and willingness to try through patches/gum (56%) and technology-based (61%) approaches. Youth exiting foster care are at high risk for smoking and other tobacco product use, as well as dependence, yet are rarely screened for use or advised to quit. As tobacco use remains among the most preventable causes of mortality and morbidity, future work should involve implementation of screening within child welfare and tailoring interventions to the unique needs of this population. The current results underscore a missed opportunity to promote public health in a vulnerable population. Highlights: Assessment of tobacco use by youth in foster care is scarce in both child welfare settings and the research literature. To date, studies of alternative tobacco product use in this population have been limited in scope. We assessed combustible and alternative tobacco use, as well as nicotine dependence and preferred cessation methods. Youth exiting foster care are at high risk for tobacco product use, yet are rarely screened for use or advised to quit. These results underscore a missed opportunity to promote public health in a vulnerable population.